Tribology Study on Elastomers - Hakami, Ferial (Curtin University, 2018)
A comprehensive experimental and analytical study is done on tribological behaviour of elastomers. According to the results, ascending rate of wear and friction changes with variation of operating variables and mechanical properties. New approaches are described for a better understanding of wear and friction process. Furthermore, to predict the wear rate a non-linear equation is developed by quantifying contribution of operating variables and mechanical properties. This study provides enhanced insight into elastomers wear in practice.